Parasitic Myoma: A Very Rare Case Report aAnd Review of Literature - Khan, Md Manir Hossain; Sultana, Jobaida (Journal of Surgical Sciences, 2019)
A 32 years old unmarried women presented with periumbilical colickey abdominal pain which shiftted to the right iliac fossa with anorexia, vomiting and low grade fever. She had history of open myomectomy 4 years back for menorrhagia with multiple fibroids (myomas). On examination, the pointing sign, Rovsing's sign, McBurney's sign &Blumberg's sign were positive. Then she was diagnosed as a case of acute appendicitis. Ultrasonography revealed nothing significant. Appendicectomy was done through right Grid Iron incision. Appendix was found inflammed, swollen and there was collection of fluid in the peritoneal cavity. During closure, incidentally a solid mass about 5 ><4 ><2.5 cm was found exterior to the peritoneum near the incision at the abdominal wall. The mass was excised. Subsequently histopathotology confirmed a leiomyoma (Myoma or parasitic fibroid). The parasitic myoma may develop spontaneously as pedanculatedsubcerousmyomaloose their uterine blood supply or iatrogenically from retained fragment of myoma from previous myomectomy or hysterectomy and get blood supply from abdominal wall. Even small bits displaced into the abdominal cavity can result in parasitic fibroids. This case is reported here to give emphasis on the surveilence of parasitic myoma during myomectomy or hysterectomy for fibroid uterus and all tissue pieces that are morcellated should be delligently removed for the prevention of further development of parasitic myoma. Journal of Surgical Sciences (2013) Vol. 17 (1) : 50-53